The Impact of Using Flashcards on Letter Comprehension Among Kindergarten Students A Case Study of Teachers' Perspectives in Nasiriyah City, Iraq. - Rheema, Ass.Lec Malak Basheer (Thi Qar Arts Journal, 2024)
This study aims to evaluate the impact of using flashcards in teaching Arabic letters to kindergarten students in the city of Nasiriyah from the perspective of teachers. A questionnaire was distributed to 21 kindergarten teachers to assess the impact of flashcards on letter comprehension and the teachers’ opinions and experiences in using this educational tool. The results showed a significant consensus on the effectiveness of flashcards in teaching letters, indicating that they help accelerate letter learning, better remind children of them, improve their language skills, and increase their motivation to learn. The teachers also provided recommendations to improve the use of flashcards, such as developing diverse and attractive cards, offering effective training for teachers in their use, and integrating them with other teaching methods. The study demonstrates that using flashcards is effective in teaching Arabic letters to kindergarten students, contributing to achieving the best educational outcomes in this field.